Analysis Professional Characteristic Of Nutrisionis A Literature Review - Dahlia Dian Paramita; izzatsaltsa maya azmi; Devina Ramadhanty Wirakusuma; Nuril Adh-har; Erianto Fanani; Ronal Surya Aditya; Putri Dwinita Haryono (STIKes Kepanjen, 2023)
Background: Health care professionalism is central to safe and effective health care and ensures the public of quality health care. Modern healthcare requires integrated care from a multidisciplinary team working across different cultures, contexts, and settings, especially a nutritionist. This multidisciplinary background means that healthcare professionals must have a shared understanding of what professionalism means. A nutritionist health worker must certainly master skills such as honesty, integrity and loyalty at work. Methode : This article is a systematic review of the literature conducted in accordance with the PRISMA declaration. The PRISMA declaration contributes to the clarity and transparency of systematic review reporting. The analysis methods and inclusion criteria for this study were established. Purpose: This article review aims to find out what attitudes a nutritionist should have. So that nutritionists have the same competence as each other. Conclusion: Each health worker will have their own professional attitude according to their profession. For example, nutritionists who must have a professional attitude, honesty, integrity in their work. This attitude is useful for showing how our skills are in front of others.